Impact of a community-based diabetes self-management program on key metabolic parameters - Johnson C; Ruisinger JF; Vink J; Barnes BJ (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Objective: Characterize the impact of a pharmacist-led diabetes self-management program on three key metabolic parameters: glycosylated hemoglobin (HbA1c), low-density lipoprotein cholesterol (LDL-C), and mean arterial blood pressure (MAP) among employee health program participants. Methods: A self-insured company in the Kansas City metropolitan area began offering a pharmacist-led diabetes self-management program to eligible company employees and their dependents in 2008. A retrospective pre-post analysis was conducted to determine if the program affected key metabolic parameters in participants by determining mean change after one year of participation. Results: Among 183 program participants, 65 participants met inclusion criteria. All three key metabolic parameters were significantly reduced from baseline to one year of program participation: HbA1c decreased from 8.1% to 7.3% (p=0.007); LDL-C decreased from 108.3 mg/dL to 96.4 mg/dL (p=0.009); and MAP decreased from 96.1 to 92.3 mm Hg (p=0.005). Conclusions: The pharmacist-led diabetes self-management program demonstrated significant reductions in HbA1c, LDL-C, and MAP from baseline to one year of program participation. Improvements were statistically significant and clinically relevant for each parameter. Previous studies indicate these reductions may cause reduced overall healthcare costs.